Restriction site mapping analysis of the adenomatous poliposis coli (APC) gene in human colorectal system - Chung, James Yaw Ming. (Universiti Malaysia Sarawak (UNIMAS), 2005)
Adenomatous Poliposis Coli (APC) anomalies are considered to playa gate-keeping role in colorectal tumorigenesis. Even though APC gene is extensively studied, there is a lack in effort towards creating a highly reproducible and less costly approach to diagnose APC anomalies. In this research, the APC cDNA fragments from the normal and tumour colorectal specimens are subjected to mutational analysis via restriction enzyme site characterization. Restriction digestions using AluI, HaeIII, Hinfl, HincH, HpaII, MboI, NdeI, RsaI, TaqI, and Trn9I were performed on all eight APC fragments of normal and tumour specimens accordingly. Restriction site map for the gene was constructed whereby assay on APC 2, APC 5, and APC 6 had generated differential restriction site pattern. Tumour APC 2 was showing aberrancy on RsaI, Hinfl, Trn9I, HaeIII, and HpaH; whereas tumour APC 5 was aberrant on AluI, and tumour APC 6 was aberrant on TaqI. This will facilitate the recognition of potential mutation marker to screen for APC aberrancy, allowing the comparative study between APC restriction site pattern of normal and tumour system.